2017
DOI: 10.1063/1.4984113
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Drude polarizable force field onto a multipole and induced dipole model

Abstract: The induced dipole and the classical Drude oscillator represent two major approaches for the explicit inclusion of electronic polarizability into force field-based molecular modeling and simulations. In this work, we explore the equivalency of these two models by comparing condensed phase properties computed using the Drude force field and a multipole and induced dipole (MPID) model. Presented is an approach to map the electrostatic model optimized in the context of the Drude force field onto the MPID model. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 85 publications
(115 reference statements)
0
55
0
Order By: Relevance
“…Various method developments, already present in the Tinker community, will be integrated in the next version of the code, keeping in mind the mandatory philosophy to include only well-understood and scalable techniques. The high-performance implementation of additional multipolar polarizable force fields will be performed including the SIBFA 26 (in progress), MPID 96 (multipole and induced dipoles, the mapping of the CHARMM Drude polarizable force field on induced dipoles) and AMOEBA 2 models. Efforts will also be devoted to the porting of the third generation GEM (Gaussian Electrostatic Model) polarizable force field that relies on frozen distributed densities.…”
Section: Discussionmentioning
confidence: 99%
“…Various method developments, already present in the Tinker community, will be integrated in the next version of the code, keeping in mind the mandatory philosophy to include only well-understood and scalable techniques. The high-performance implementation of additional multipolar polarizable force fields will be performed including the SIBFA 26 (in progress), MPID 96 (multipole and induced dipoles, the mapping of the CHARMM Drude polarizable force field on induced dipoles) and AMOEBA 2 models. Efforts will also be devoted to the porting of the third generation GEM (Gaussian Electrostatic Model) polarizable force field that relies on frozen distributed densities.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent work [ 133 ] analytically showed that significant additional computational costs can be justified in multi-scale free energy simulations, if the sampling method exhibits a higher phase space overlap with the target QM Hamiltonian. Thus, it can be expected that polarizable force fields and, ultimately, quantum-mechanical methods will play an increasing role in free energy calculations [ 134 , 135 , 136 , 137 , 138 , 139 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, polarizable force fields should in principle provide higher accuracy in our approach as fixed charge force-fields are limited in their ability to account for the change in charges during the course of the simulation. A theoretically-promising method to handle this effect is to use polarizable force fields such as AMOEBA [68] [69] , Drude [70] or a recently formulated multipole and induced dipole (MPID) model [71]. Any of these polarizable models should improve the pKa prediction results of our method, given high quality polarizable force field parameters for general drug-like molecules are available.…”
Section: Resultsmentioning
confidence: 99%